무용사회화 주관자가 무용전공대학생의 무용참가 및 무용성취에 미치는 영향 - 김경식(Kyung-Sik Kim); 현보람(Bo-Ram Hyun); 김정련(Jeong-Ryeon Kim); 윤민숙(Min-Sook Yun) (한국콘텐츠학회논문지, 2013)
This paper focuses on how a dance socialization supervisor affects dance participation and achievement of university students majoring in dance. Dance majors in their senior year were set as the population and 265 samples were selected through purposive sampling. The validity of the results were confirmed through the use of factor analysis and reliability test with a result of over 0.779. The data collected from the test was analyzed through factor analysis, reliability test and regression analysis using the SPSSWIN 18.0 program. The conclusions are as follows. First, dance socialization supervisor affects dance participation of university students majoring in dance. Second, dance socialization supervisor affects achievement of dance majors. Third, dance participation affects achievement in dance. 이 연구는 무용사회화 주관자가 무용전공생의 무용참가 및 무용성취에 미치는 영향을 규명하는데 목적이 있다. 이 연구는 2013년 현재 4년제 대학 무용학과에 재학 중인 무용전공생들을 모집단으로 선정한 다음, 유의표집법(Purposive sampling)을 이용하여 265명을 표집 하였다. 타당도 및 신뢰도는 요인분석 및 신뢰도분석을 통해 검증하였으며, 신뢰도는 계수는 .779이상으로 나타났다. 자료처리는 SPSSWIN 18.0 프로그램을 활용하여 요인분석, 신뢰도분석, 회귀분석 등이 활용되었다. 결론은 다음과 같다. 첫째, 무용사회화 주관자인 부친, 모친, 형제자매, 친구, 학교교사는 무용전공생의 무용참가에 영향을 미친다. 둘째, 무용사회화 주관자인 부친, 모친, 형제자매, 친구, 학교교사는 무용성취에 영향을 미친다. 셋째, 무용전공생의 무용참가는 무용성취에 영향을 미친다.